Experience of transcatheter device closure of atrial septal defect in a tertiary care institute - Muhammad Younas; Ahsan Beg; Tauseef Asma; Baqir Maqbool (Journal of the Pakistan Medical Association, 2021)
Objective: To share our experience of transcatheter device closure of secundum atrial septal defect in children and adults. Methods: This descriptive cross-sectional study was conducted at department of Paediatric Cardiology Ch. Pervaiz Elahi Institute of Cardiology Multan from 2011 to September 2019. Patients with moderate to large ASD secundum without severe pulmonary hypertension were studied. All procedures were performed under general anaesthesia and trans-Oesophageal echo guidance. Success and safety of procedure were evaluated. Results: During study period, a total of 75 patients underwent ASD device closure. Mean age was 25 ± 1.53 (4 -54 years) and male to female ratio 1:2. Mean defect was 20.38 ± 0.58 (09 to 32 mm). Large defects (> 25 mm) were 17 (22.7 %). Significant PS (> 30 mm Hg) observed in three and valvuloplasty performed. Device size was selected on the basis of TOE measurement + 4-5 mm. Balloon sizing was performed in only three patients. Amplatzer septal occluder was used in 80 %. Balloon assisted technique was used in 09 (12 %) patients. All the procedures were successful except two (2.7 %) where device embolized and retrieved by surgery. Transient arrhythmias were observed in 05 (6.6 %) and small pericardial effusion which was managed conservatively in one patient. There was no procedure related mortality. Conclusion: Transcatheter closure of moderate to large ASD secundum in children and adults is a safe procedure. Among the major events, device embolizaion was common. Other complications were rare including small pericardial effusion and transient arrhythmias. Continuous...